2020
DOI: 10.1002/lol2.10149
|View full text |Cite
|
Sign up to set email alerts
|

Organic sulfur: A spatially variable and understudied component of marine organic matter

Abstract: Scientific Significance StatementOrganic sulfur is a significant component of cellular material and can be a preferred organic matter source for marine microorganisms. We have limited direct measurements of organic sulfur concentrations and these measurements have not been considered in conjunction with mass spectrometry-based assessments of sulfur-containing organic compounds in seawater. Our results reveal the concentration of organic sulfur was highly variable with depth and latitude in the western Atlantic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…1, B and C). A recent study in the western Atlantic Ocean reported 6% of DOS formulas in total DOM and suggested that the SPE DOM did not capture a representative fraction of DOS (45). We detected a similar proportion of DOS formulas for the fully oxygenated deep ocean reference sample included in our study (NEqPIW DOS formulas, 8%; Fig.…”
Section: Dom Accumulating In the Black Sea Is Enriched In Autochthono...supporting
confidence: 80%
See 1 more Smart Citation
“…1, B and C). A recent study in the western Atlantic Ocean reported 6% of DOS formulas in total DOM and suggested that the SPE DOM did not capture a representative fraction of DOS (45). We detected a similar proportion of DOS formulas for the fully oxygenated deep ocean reference sample included in our study (NEqPIW DOS formulas, 8%; Fig.…”
Section: Dom Accumulating In the Black Sea Is Enriched In Autochthono...supporting
confidence: 80%
“…5 and Table 1). This is opposite to depth distributions in major oxic ocean basins, where DOS accumulates preferentially in the surface waters, presumably due to microbial production of DOS near the sea surface and preferential decomposition of these compounds before export to the deep ocean (44,45). On the molecular level, 18% of all molecular formulas and 52% of the molecular formulas that exclusively occurred in the anoxic waters of the Black Sea contained sulfur (Fig.…”
Section: Dom Accumulating In the Black Sea Is Enriched In Autochthono...mentioning
confidence: 86%
“…In shallow (0-150 m depth) waters, the loss of apparent DOS SPE and DOC, increase in C:S ratios, and near-constant δ 34 S and δ 13 C values with depth can be readily explained by the rapid uptake and/or remineralization of phytoplankton-derived labile DOS compounds without fractionation. The preferential loss of sulfur relative to carbon is similar to that observed for nitrogen and phosphorous over the same depth by other studies (1,65) and is unsurprising given that a majority of organic sulfur is present as diverse bioavailable components like thiols, sulfonates, or thiophenes (6,7). The minimal isotopic fractionation also agrees with studies of both specific degradation reactions (38) and bulk trophic level effects (66,67).…”
Section: Discussionsupporting
confidence: 84%
“…Pohlabeln et al calculated the flux of these highly recalcitrant DOS species as a significant source to benthic DOS SPE and by extension to water column DOM SPE (13). While the proportion of DOM molecules that contain sulfur is not known precisely, estimates from molecular formulas of SPE DOM imply it could be ∼5-10% (7). Such numbers suggest that porewater-sourced, sulfurized molecules could represent an overlooked subcycle within DOM and might also help to explain why some components of DOM SPE have surprisingly long lifetimes, clarifying connections between DOC and DOS cycles in the ocean (25).…”
Section: Significancementioning
confidence: 99%
“…Clinical trials have shown that S‐containing drugs can be used for the treatment of Alzheimer's disease, [12] Parkinson's disease, [13] depression and anxiety, [14] AIDS, [15] cancer [16] and other diseases [17] . Moreover, sulfur‐containing compounds are applied in other fields, such as biological, [18] organic, [19,20] and materials chemistry [21] …”
Section: Introductionmentioning
confidence: 99%